Pan-immune-inflammation value and systemic immune-inflammation index: Are they useful markers in sarcoidosis? SII and PIV in sarcoidosis - Ertürk , Adem; Balcı , Aydın (Journal of Surgery and Medicine, 2023)
Background/Aim: Sarcoidosis is a multisystem inflammatory disease characterized by the infiltration of various organs. Due to the lack of a widely-accepted biomarker, researchers have explored alternative and previously unexplored parameters in sarcoidosis. This study aimed to investigate the utility of various markers, including the systemic immune-inflammation index (SII) and pan-immune-inflammation value (PIV), in patients with sarcoidosis. Methods: A case-control study was conducted between January 2019 and February 2023. The study included 75 patients diagnosed with sarcoidosis, and 93 healthy individuals matched for age, sex, and body mass index. Sarcoidosis-related features, such as lung stage and extrapulmonary involvement, were recorded. The researchers investigated SII, PIV, procalcitonin, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), other biochemical results, and complete blood counts (including neutrophil, lymphocyte, monocyte, platelet counts, hemoglobin, mean platelet volume [MPV], and red cell distribution width [RDW]). Results: The age and sex distribution were similar in both the case and control groups (P=0.258 and P=0.196, respectively). The patient group had a significantly lower absolute lymphocyte count than the control group (P=0.035). Patients’ RDW (P=0.007), platelet-to-lymphocyte ratio (P=0.028), and ESR (P<0.001) values were significantly higher compared to controls. No significant difference was observed between the two groups regarding other variables, including PIV and SII. There was a significant weak positive correlation between PIV and lung stage, as well as between MPV and the presence of erythema nodosum. Conclusion: PIV and SII values in patients with sarcoidosis were similar to controls. The positive correlations between PIV and lung stage and between MPV and erythema nodosum suggest potential relationships with sarcoidosis-related features and demonstrate the value of these readily available and inexpensive markers in patient management. Comprehensive studies are needed to clarify whether SII and/or PIV can be used to assess the characteristics of patients with sarcoidosis.